Examining The Relationship between Shift Work and Diabetes Mellitus among Nurses: An Evidence-based Case Report - Arifianto, Angga; Widyahening, Indah Suci; Khoe, Levina Chandra; Mokoagow, M. Ikhsan (UI Scholars Hub, 2024)
Background : Work shifts could cause numerous health problems, such as sleep disorders, weight gain disorders, and unhealthy food intake consumption, leading to obesity and changes in blood glucose levels, that eventually lead to diabetes mellitus. This evidence-based case report aims to provide an evidence of association between shift work and the risk of diabetes mellitus among nurses. Methods : We performed a literature searching from Pubmed, Embase, Cochrane, Scopus, and Google Scholar in September 2023 using keywords ‘shift work’ AND ‘diabetes’ AND ‘nurse’. We included studies that assessed the association between shift work and diabetes among nurses using observational studies, meta-analysis, and systemic review as their study design. The outcome variable was the odd ratio or the relative risk of developing diabetes. We excluded cross-over studies, clinical trials, and cross-sectional studies. In addition, quality assessment was conducted according to The Oxford Center for Evidence-Based Medicine (OCEBM). Results : After title and abstract screening, we found seven out of twenty articles with a total of 689,273 participants. Among these articles, there were three cohort studies which found an increased relative risk (1.08 to 2.60) of diabetes among nurses who worked night and rotating shifts compared to those who did not. Another evidence from two cohort studies and one meta-analysis identified that nurses who worked in full shifts had an increased risk of diabetes (1.05 to 3.60) than those who worked non-shifts. Factors affecting the risk of diabetes were gender, unhealthy lifestyle, sleep disorders, and shift work duration (≥10 years). Conclusions : Shift work in nurses has a significant association with the risk of diabetes mellitus. Nurses had been working shift work for more than 10 years, particularly on night shift, had a higher risk compared to those who had been working for less than 10 years without night shift. Additional factors such as obesity, smoking, lack of physical activity, unhealthy diet, and sleep disorders would increase the risk of diabetes mellitus.